Cytokine Profiles and Antibody Response Associated to Choclo Orthohantavirus Infection - Salinas, Tybbysay P.; Garrido, Jose L.; Salazar, Jacqueline R.; Gonzalez, Publio; Zambrano, Nicole; Fuentes-Villalobos, Francisco; Bravo, Felipe; Fica-Leon, Victor; Salas-Burgos, Alexis; Calvo, Mario; Alvarez, Raymond; Armien, Blas; et al. (Frontiers in Immunology, 2021)
Background New World Hantaviruses (NWHs) are the etiological agent underlying Hantavirus cardiopulmonary syndrome (HCPS), a severe respiratory disease with high mortality rates in humans. In Panama, infections with Choclo Orthohantavirus (CHOV) cause a much milder illness characterized by higher seroprevalence and lower mortality rates. To date, the cytokine profiles and antibody responses associated with this milder form of HCPS have not been defined. Therefore, in this study, we examined immune serological profiles associated with CHOV infections. Methods For this retrospective study, sera from fifteen individuals with acute CHOV-induced HCPS, were analyzed alongside sera from fifteen convalescent phase individuals and thirty-three asymptomatic, CHOV-seropositive individuals. Cytokine profiles were analyzed by multiplex immunoassay. Antibody subclasses, binding, and neutralization against CHOV-glycoprotein (CHOV-GP) were evaluated by ELISA, and flow cytometry. Results High titers of IFNg, IL-4, IL-8, and IL-10 serum cytokines were found in the acute individuals. Elevated IL-4 serum levels were found in convalescent and asymptomatic seropositive individuals. High titers of IgG1 subclass were observed across the three cohorts analyzed. Neutralizing antibody response against CHOV-GP was detectable in few acute individuals but was strong in both convalescent and asymptomatic seropositive individuals. Conclusion A Th1/Th2 cytokine signature is characteristic during acute mild HCPS caused by CHOV infection. High expression of Th2 and IL-8 cytokines are correlated with clinical parameters in acute mild HCPS. In addition, a strong IL-4 signature is associated with different cohorts, including asymptomatic individuals. Furthermore, asymptomatic individuals presented high titers of neutralizing antibodies.